2009
DOI: 10.1537/ase.081219
|View full text |Cite
|
Sign up to set email alerts
|

Craniometric divergence history of the Japanese populations

Abstract: The Japan Islands, a small island chain on the western rim of the circum-Pacific region, have experienced several cultural contacts and human migrations from northern and eastern continental Asia. In this study, craniometric diversification of Asian peoples was assessed using the R-matrix method based on 21 metric traits in 25 representative male and female samples of prehistoric and modern northeastern and eastern Asians, including inhabitants of the Japan Islands. The prehistoric series show, in general, gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 59 publications
3
29
1
1
Order By: Relevance
“…The Jomon and Lagoa Santa were plotted nearby in the principal coordinate plots when we weighted 0.30 for Lagoa Santa (see Figure 9, Figure 10). These results indicate that the ancient East Asians have more than expected craniofacial variations (also see Ishida et al, 2009), but the New World populations show less than expected craniofacial variations (Table 5, Table 6). It appears that New World samples are more newly derived populations than are ancient East Asian populations.…”
Section: Resultsmentioning
confidence: 75%
“…The Jomon and Lagoa Santa were plotted nearby in the principal coordinate plots when we weighted 0.30 for Lagoa Santa (see Figure 9, Figure 10). These results indicate that the ancient East Asians have more than expected craniofacial variations (also see Ishida et al, 2009), but the New World populations show less than expected craniofacial variations (Table 5, Table 6). It appears that New World samples are more newly derived populations than are ancient East Asian populations.…”
Section: Resultsmentioning
confidence: 75%
“…Table 3 shows the estimated F st (h 2 = 0.4-0.6) for limb bone measurements and other F st values. The result of the estimated F st of 0.432-0.336 shows that the variation of limb bone measurements across regions is rather large, at approximately two or three times the low levels of interregional variation (0.078-0.180) in analyses of cranial and dental data Toma et al, 2007;Komesu et al, 2008;Ishida et al, 2009). …”
Section: Resultsmentioning
confidence: 96%
“…In addition, the authors had an opportunity to examine approximately 260 Okhotsk skeletal remains in Hokkaido University Museum from 2003. Metric and nonmetric data of cranial and dental traits in the Okhotsk area and northeast Asian samples were reported elsewhere (Ishida, 1990(Ishida, , 1992(Ishida, , 1993(Ishida, , 1994(Ishida, , 1995(Ishida, , 1996(Ishida, , 1997Ishida and Dodo, 1996;Ishida and Kondo, 1999). Recently, Hirofumi Matsumura of Sapporo Medical University, one of the authors, reported metric features of the femur in the Okhotsk people .…”
Section: Introductionmentioning
confidence: 87%
“…In that study, she found low heritability estimates of most bilateral breadth measurements, while cranial length and height dimensions have heritability values ranging between 0.102 and 0.729 (Carson, 2006). Relethford and Blangero (1990) concluded that as long as the narrow-sense heritability for a traits was greater (Hanihara, 2008;Ishida et al, 2009) overall average heritabilities for craniometric traits of h 2 = 0.55 to compute the R-matrix.…”
Section: Methodsmentioning
confidence: 96%
“…An R-matrix provides estimates of genetic similarities and distances within and among populations relative to the contemporary means of allele frequencies in a region (Relethford and Harpending, 1994). Recently, the R-matrix/ Relethford-Blangero method has been applied to quantitative morphological traits to search population relationships and/or population structure by many researchers (Relethford, 1994;Relethford and Harpending, 1994;Powell and Neves, 1999;Steadman, 2001;GonzĂĄlez-JosĂ© et al, 2001, 2005Roseman and Weaver, 2004;Stojanowski, 2004Stojanowski, , 2005Ishida, 2005, 2009;Hanihara, 2008;Ishida et al, 2009). Continuing this body of literature, these methods will be applied to the present study.…”
Section: Methodsmentioning
confidence: 97%